Resource Allocation for OFDM-Based Multi-Destination Relay Networks with Direct Links - Xiaoyi Liu; Li Chen; Xin Zhang; Dacheng Yang (2011 IEEE Global Telecommunications Conference - GLOBECOM 2011, 2011)
In this paper, we study the joint resource allocation for the multi-destination amplify-and-forward relay network with direct source-to-destination links based on orthogonal frequency division multiplexing (OFDM) transmission. We aim to maximize the sum rate by jointly optimizing power allocation, subcarrier pairing, user assignment and transmission mode classification subject to the individual power constraints for the source and relay nodes. The optimization problem is solved based on dual method and a near-optimal joint resource allocation scheme is proposed. Besides, two sub-optimal schemes with reduced complexity are presented. Finally, simulation results show that the proposed near-optimal scheme outperforms other sub-optimal resource allocation schemes.